2023
DOI: 10.3389/fpsyg.2023.1141045
|View full text |Cite
|
Sign up to set email alerts
|

Factors and barriers that influence the matriculation of underrepresented students in medicine

Abstract: Despite many initiatives over more than 4 decades, the diversity of United States physicians still does not reflect the diversity of the United States population. The present study undertakes a literature review of the last 30 years to investigate barriers and protective factors underrepresented college students encounter as applicants for medical school. Known barriers that influence matriculation into medical school were analyzed such as academic metrics and test scores. Additionally, elements that are less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…Barriers unique to HEGs can often contribute to feelings of inadequacy and deeply impact student’s sense of belonging, and therefore retention, in STEM. This is exacerbated by negative social influence and systemic oppression (Estrada et al, 2018; Tello & Goode, 2023), and can culminate into feelings of not belonging in STEM. Meanwhile, studies have shown that underserved students that develop a scientific identity (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Barriers unique to HEGs can often contribute to feelings of inadequacy and deeply impact student’s sense of belonging, and therefore retention, in STEM. This is exacerbated by negative social influence and systemic oppression (Estrada et al, 2018; Tello & Goode, 2023), and can culminate into feelings of not belonging in STEM. Meanwhile, studies have shown that underserved students that develop a scientific identity (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we used two old terms, LEP for patients [ 34 ] and ESL for the higher education applicants [ 14 ]. Second, multilevel intersectionality, i.e., the sociodemographic, sociocultural, and schooling characteristics may significantly limit the number of resources available to ESL students [ 8 , 14 ]. Furthermore, English learners are subject to the effects of local, state and federal policies shaping their academic experiences [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Language fluency is an advantage point for native English-speaking applicants. PA program admission processes and committees could also be influenced by implicit or explicit biases against candidates with differing linguistic or cultural backgrounds [ 8 ] which necessitates implicit bias training for admissions teams as well as diversifying the admissions teams. Holistic admissions are aimed at optimizing equity in the admissions process and have been described in the medical and PA education literature [ 19 , 37–40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations